The Effect of Residence in Highlands and Industrial Areas on the Incidence of Hypertension - Hasabi, Faris; Romadhon, Yusuf Alam (Newinera Publisher, 2024)
Hypertension is a measurement of systolic blood pressure (SBP) ≥140 mmHg and/or diastolic blood pressure (DBP) ≥90 mmHg. According to WHO data, the number of adults with hypertension has doubled from 650 million in 1990 to 1.3 billion in 2019. The prevalence in Indonesia in 2018 was around 34.1% and in Kendal it continues to increase every year. People who live in the highlands are at risk of developing hypertension due to differences in the body's physiological processes with people who live in the lowlands. Various types of air pollutants such as particulate matter (PM) are widely recorded as being associated with cardiovascular disease, especially in industrial areas and big cities. This study is to analyze the effect of proximity to highland residences and industrial areas on the incidence of hypertension in Kendal Regency. This study uses observational analytics with a cross-sectional research design. The sampling technique used is purposive sampling. Univariate and bivariate analysis using Chi-Square test. Significant results were obtained based on the Chi-Square test on the effect of residence in the highlands and industrial areas on the occurrence of hypertension with a p-value of 0.000 ( p-value <0.05). This study shows the effect of proximity to residence in the highlands and industrial areas on the occurrence of hypertension in Kendal Regency.